Quality parameters of minced meat and raw formed products on Bosnian and Herzegovinian market - Muftić, Emina; Čaklovica, Kenan; Tahirović, Dinaida; Muftić, Abdullah; Čaklovica, Faruk (2020)
The aim of this research was to examine physicochemical parameters of finished and semi-finished meat products: minced meat (beef, pork and mixed meat) and raw formed meat products (ćevapi, patties/burgers and sujuk sausages), and to determine quality parameters of these products on the Bosnia and Herzegovina market. Examined parameters included: protein content, fat, collagen in meat proteins and salt (NaCl). We analysed 282 samples of these products and found deviations with regard to the applicable Ordinance on minced meat and semi-finished and finished meat products of “The Law on Food of Bosnia and Herzegovina” in all parameters, except salt (NaCl). The majority of deviations referred to the content of collagen in meat proteins, with as much as 21.98 % of examined samples in violation of the applicable legislation.
Cilj istraživanja je bio ispitati fizikalno-kemijske parametre proizvoda i poluproizvoda od sirovog mesa: mljeveno meso (juneće, svinjsko i miješano) i sirovi oblikovani proizvodi (ćevapi, pljeskavice i sudžukice) i parametre kvalitete ovih proizvoda na bosansko-hercegovačkom tržištu. Ispitivani parametri su: sadržaj proteina, masti, kolagena u proteinima mesa i soli (NaCl). Ispitana su 282 uzorka navedenih proizvoda, te su utvrđena odstupanja u svim parametrima, izuzev soli (NaCl), u odnosu na važeći Pravilnik o usitnjenom mesu, poluproizvodima i proizvodima mesa. Najviše odstupanja je bilo u sadržaju kolagena u proteinima mesa, gdje čak 21,98 % ispitanih uzoraka nije bilo u skladu sa normativima.
Ziel dieser Untersuchung war es, die physikalisch-chemischen Parameter von fertigen und halbfertigen Fleischprodukten: Hackfleisch (Rind-, Schweine- und Mischfleisch) und roh geformte Fleischprodukte (Ćevapi, Burger und Würste) sowie die Qualitätsparameter dieser Produkte auf dem bosnischen und herzegowinischen Markt zu untersuchen. Es wurden folgende Parameter untersucht: Gehalt an Proteinen, Fett, Kollagen in Fleischproteinen und Salz (NaCl). Es wurden 282 Proben dieser Produkte analysiert. Bei allen Parametern, mit Ausnahme von Salz (NaCl), wurden in Bezug auf die gültige Verordnung über Hackfleisch und halbfertige und fertige Fleischprodukte Abweichungen festgestellt. Die Ergebnisse dieser Untersuchungen zeigten die meisten Abweichungen beim Kollagengehalt in Fleischproteinen; dabei entsprach sogar 21,98 % der untersuchten Proben nicht der gültigen Gesetzgebung.
El objetivo de este trabajo fue examinar los parámetros fisicoquímicos de los productos cárnicos y de los productos semiacabados de carne cruda: la carne picada (carne de res, de cerdo y carne mixta) y de los productos cárnicos formados crudos (ćevapi, hamburguesas y salchichas) y los parámetros de calidad de estos productos en el mercado de Bosnia y Herzegovina. Los parámetros examinados son: el contenido de proteínas, las grasas, el colágeno en las proteínas de carne y la sal (NaCl). Fueron analizadas 282 muestras de los productos mencionados y hubo desviaciones en todos los parámetros, excepto la sal (NaCl), en relación con el Reglamento vigente sobre la carne picada, los productos cárnicos semiacabados y los productos cárnicos. La mayoría de las desviaciones fue en el contenido del colágeno en las proteínas de carne, donde hasta 21,98% de las muestras fueron incompatibles con la regulación normativa.
Lo scopo della ricerca consisteva nell’esaminare i parametri fisico-chimici dei prodotti finiti e dei semilavorati di carne cruda: carne macinata (di bovino, suino e mista) e prodotti di carne macinata cruda (ćevapi, pljeskavice e sudžukice), oltre ai parametri qualitativi di questi prodotti sul mercato bosniaco-erzegovese. La ricerca ha esaminato i seguenti parametri: contenuto di proteine, di grassi, di collagene nelle proteine della carne e di sale (NaCl). Nei 282 campioni analizzati sono stati accertati scostamenti in tutti i parametri esaminati, ad eccezione del sale (NaCl), rispetto al vigente Regolamento sulla carne macinata, i semilavorati e i prodotti a base di carne. I maggiori scostamenti sono stati riscontrati in ordine al contenuto di collagene nelle proteine della carne, dove ben il 21,98% dei campioni esaminati è risultato non a norma.
Bibliografija: 15 jed.
Sažetak ; Abstract ; Zusammenfassung ; Resumen ; Riassunto.
Keywords: Mljeveno meso -- Kvaliteta mesa -- Kolagen -- Fizikalno-kemijska svojstva -- Mesni proizvodi